Can science and technology save China ? - Greenhalgh, Susan; Zhang, Li (New York Cornell University press, 2020)
This study of the intimate connections between science and society in China shows that science and technology, far from saving China, as the country's leaders promise, are producing unanticipated, often deeply disturbing effects.
Keywords: Technology and state China; Technology social aspects China; Science social aspects